Building Satisfaction and Loyalty of Go-Jek User Communities in Cibodas District, Tangerang City - Eneng Wiliana; Nining Purwaningsih (Jurnal Pemasaran Kompetitif, 2023)
People's mobility is currently increasing, of course, requires transportation facilities that can facilitate movement and movement from one place to another quickly, even though the distance is long. The rapid and practical development of internet-based technology has given rise to an online application-based transportation innovation supported by communication technology via smartphones. This online application-based transportation is a combination of motorcycle taxi transportation services and communication technology. This study aims to examine the effect of service quality on customer satisfaction and loyalty of users of Gojek online motorcycle taxi transportation services, especially the people in Cibodas District, Tangerang City, amidst the many competition of similar companies. This research is a survey research. The population in this study are all customers who use Gojek online motorcycle taxi transportation in Cibodas District, Tangerang City. This research technique uses non-probability sampling. The researcher uses incidental sampling with a total of 150 respondents. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple regression. The statistical test results show that customer satisfaction has a positive and significant effect on customer loyalty to gojek. This research also shows how important satisfying service is so that customers have high loyalty and customers do not switch to other online motorcycle taxi applications.y Key : Service Quality, Customer Satisfaction, Customer Loyalty